2022
DOI: 10.1002/eap.2505
|View full text |Cite
|
Sign up to set email alerts
|

Developing fine‐grained nationwide predictions of valuable forests using biodiversity indicator bird species

Abstract: The use of indicator species in forest conservation and management planning can facilitate enhanced preservation of biodiversity from the negative effects of forestry and other uses of land. However, this requires detailed and spatially comprehensive knowledge of the habitat preferences and distributions of selected focal indicator species. Unfortunately, due to limited resources for field surveys, only a small proportion of the occurrences of focal species is usually known. This shortcoming can be circumvente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 66 publications
(106 reference statements)
0
19
0
Order By: Relevance
“…For Slovenia, Nagel et al [430] concluded that integrated management practiced on a large scale is insufficient to maintain viable populations of species dependent on naturally dynamic and old-growth forests. The same conclusion has been found in Finland [431,432] and Sweden [433]. Kuuluvainen et al [268] expressed this kind of mismatch as "The development of retention practices in Finland indicates that the aim has not been to use ecological understanding to attain specific ecological sustainability goals, but rather to define the lowest level of retention that still allows access to the market".…”
Section: Integration-segregation-triadmentioning
confidence: 72%
“…For Slovenia, Nagel et al [430] concluded that integrated management practiced on a large scale is insufficient to maintain viable populations of species dependent on naturally dynamic and old-growth forests. The same conclusion has been found in Finland [431,432] and Sweden [433]. Kuuluvainen et al [268] expressed this kind of mismatch as "The development of retention practices in Finland indicates that the aim has not been to use ecological understanding to attain specific ecological sustainability goals, but rather to define the lowest level of retention that still allows access to the market".…”
Section: Integration-segregation-triadmentioning
confidence: 72%
“…We used a 10 km buffer for background point selection (10,000 random points) for all species except Henslow's Sparrow and Northern Long‐Eared Bat, which had a 25 km buffer. The background point selection for presence only models should represent accessible area for the modeled species and, despite the low to moderate dispersal distances, we believe that the broader extent buffers are a better match to the scale of habitat selection for these volant species (Gómez‐Ruiz & Lacher, 2016 ; Monadjem et al., 2021 ; Virkkala et al., 2022 ; Zhang et al., 2018 ). These buffered regions served as the area for background point selection in all models.…”
Section: Methodsmentioning
confidence: 99%
“…A number of protected areas, a central measure of area-based conservation [14], have been introduced globally to bend the species extinction curve. Moreover, recent technological improvements allow for mapping biodiversity features at fine resolutions (e.g., 100 m × 100 m) within a large spatial extent [15], which can substantially promote fine-tuned SCP.…”
Section: Introductionmentioning
confidence: 99%